Association Between Occupational Physicochemical Exposures and Headache/Eyestrain Symptoms Among Korean Indoor/Outdoor Construction Workers - Sung Won Jung; June-Hee Lee; Kyung-Jae Lee; Hyoung-Ryoul Kim (Elsevier, 2019)
Background: Headache/eyestrain symptoms are common health problems that people experience in daily life. Various studies have examined risk factors contributing to headache/eyestrains, and physicochemical exposure was found to be a leading risk factor in causing such symptoms. The purpose of this study was to examine the relationship of headache/eyestrain symptoms with physicochemical exposure among Korean construction workers depended on worksite. Methods: This study used data from the 4th Korean Workers Conditions Survey and selected 1,945 Korean construction workers as participants. Multivariable logistic regression analysis was used to determine the relationship. Results: Exposure to vibrations among all construction workers affected the moderate exposure group [odds ratio (OR) 1.53, 95% confidence interval (CI) 1.01-2.32], the high exposure group (OR 1.77 95%CI 1.17-2.67), and the indoor high exposure group (OR 1.61, 95%CI 1.02-2.55) and among outdoor construction workers, the moderate group (OR 6.61, 95%CI 15.4-28.48) and the high group (OR 6.61, 95%CI 1.56-27.98). When exposed to mist, dust, and fumes, the indoor high exposure group was significantly affected (OR 1.63, 95%CI 1.07-2.47). All construction workers exposed to organic solvents were affected, high exposure group (OR 1.69, 95%CI 1.15-2.49) and indoor high exposure group (OR 1.77, 95%CI 1.08-2.89). The high exposure group in all construction worker (OR 1.70, 95%CI 1.20-2.42) and the indoor high exposure group (OR 1.83, 95%CI 1.17-2.89) also were affected by secondhand smoking exposure. Conclusion: Many physicochemical exposure factors affect headache/eyestrain symptoms among construction workers, especially indoor construction workers, suggesting a deficiency in occupational hygiene and health environments at indoor construction worksites. Keywords: Construction worker, Eyestrains, Headache, Physicochemical exposure